OPTIMISATION OF PROCESS PARAMETERS FOR M.A.G WELDING OF API X70M MATERIAL TO PREDICT TENSILE STRENGTH USING TAGUCHI METHOD (Nigerian Journal of Technology, 2020)
Girth welded replica of API X70M material have been produced on NG-GMAW welding technique. The particular area of interest is to develop suitable girth welding process parameter using NG-GMAW. The major aim of the work was to replicate welds having tensile strength between 650 and 680 MPa. Design of Experiment (DoE) method by Taguchi design, using some selected welding processes was adopted. Two process parameters (factors) – arc voltage and wire feed rate, (the variables), and three levels were used. The resultant joint property on tensile strength of X70M pipeline was examined. The targeted mechanical property was achieved by selecting the best process parameters.  Their effects on ultimate tensile strength – UTS was analysed using statistical technique – analysis of variance - ANOVA and Signal to Noise - S/N ratio with ‘the-bigger-the–better’ value. Validation was done using MIDAS NFX (an FEA) mechanical engineering software. In conclusion, process parameters that affects or influences the girth welded properties of API X70M under field conditions were identified. Guidance for the specifications and selection of processes that could be used in field-welding for optimum performance has been recommended. http://dx.doi.org/10.4314/njt.v39i4.17